THE BASIS OF SECURITY CHALLENGES IN NIGERIA: IMPLICATIONS FOR FOREIGN INVESTORS - Egor, Ichima (British Journal of Marketing Studies, 2014)
The issues of security challenges in Nigeria has it’s root in the cultural and political set up of the country. The ideology of different ethnic groups based on their historical background plays a major role. The Colonial masters were more interested in the economic gains that could be derived from the country rather than fashioning a united nation that evolved from different background. Potential investors in Nigeria must recognize these underlying forces that breed violence and map up strategies that can take care of them and thus enhance smooth operations of business activities.